The "ashfall" coming from Irazú volcano (Costa Rica) on december 8th 1994: a phreatic explosion? - Alvarado, Guillermo E. (2011)
During the night of December 8th, 1994, along an unstable area at the northern flank of Irazú volcano, Costa Rica, a small volcanic debris avalanche and subsequent debris flows took place, followed by an “ashfall” that reached 30 km southwest from the volcano. At that time, these processes were interpreted as the result of a phreatic ex- plosion. However, a review of the descriptions given in the technical reports and other documents of the time, together with the analysis of the geomorphology obtained from aerial photographs taken on December 20, 1994, by the Costa Rica National Geographic Institute, lead to discuss the validity of this interpretation, which although not ruled out, it seems unlikely. This paper proposes, based on the facts and information available, a new hypothesis of the occurrence of a volcanic debris avalanche resulting from a major landslide near the northern summit area. Consequently, the fo- llowing “ash” fall could be interpreted as generated by the dust produced byauto-fragmentation of the debris avalanche, so subsequently called co-debris avalanche dust-cloud deposit.